BUXGALTERIYA AUDITI - Po’latov Xudoyberdi O’ktamovich, Sattorova Feride Anvarovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
An accounting audit is the process of examining, evaluating, and controlling an organization's financial statements and accounting processes. This process is carried out to ensure the accuracy, reliability and legality of financial statements. Accounting audit is an important tool for improving the organization's financial situation, identifying financial errors and correcting them. This article provides detailed information about the basic concepts, types, process and importance of accounting audit.